IMPLEMENTASI PENDIDIKAN KARAKTER PADA BUKU AJAR BAHASA ARAB DI MADRASAH IBTIDA’IYAH - Ahmad Syagif (FASHLUNA, 2021)
The Character of education needs to be instilled in students from an early age so it needs to be integrated in learning through the teaching materials used. This is intended to change the mindset towards learning that only dwells on the cognitive domain so that it touches more on a more fundamental aspect, namely the character of students. This paper aims to identify the extent to which character education is implemented in Arabic language textbooks at Madrasah Ibtida'iyah. With a qualitative approach to the type of library research, the data were collected through documentation techniques. The main data source of this research is the Arabic language textbook for Madrasah Ibtidaiyah curriculum 2013 based on KMA No. 183 of 2019. From the analysis of the existing findings, it was found that the content of character education has been gradually integrated into the textbooks through systematic theme preparation, material selection, as well as additional content in books such as picture illustrations, and the introduction of language skills.